2004
DOI: 10.1111/j.1468-4446.2004.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Working part‐time: achieving a successful ‘work‐life’ balance?1

Abstract: The role of part-time employment in the balancing of women's employment and family lives has generated an immense literature. Using data on women working part-time and full-time in different level occupations in the British Household Panel Survey, this paper argues that it is now vital to move these balancing debates on from their location within work-family rhetoric and to re-position the study of women's working time in broader work-life discussions. Work-family debates tend to neglect a number of key domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
1
6

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 38 publications
2
118
1
6
Order By: Relevance
“…happiness and affection) in working mothers' evaluations of their everyday lives (13). Finally, mothers reported lower levels of satisfaction with leisure and social lives but higher levels of satisfaction with life as a whole (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…happiness and affection) in working mothers' evaluations of their everyday lives (13). Finally, mothers reported lower levels of satisfaction with leisure and social lives but higher levels of satisfaction with life as a whole (16).…”
Section: Discussionmentioning
confidence: 99%
“…Caring for young children has previously been shown as being associated with a lower risk for AUD (11). Other studies, both within and outside the field of alcohol research, have reported more complex associations concerning a motherhood role and outcomes in health, life satisfaction or problematic drinking (7,13,16). Having a motherhood role, combined with other social roles, influenced heavy drinking differently across countries (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, poor quality employment with low wages or irregular work hours disrupts family schedules and might increase marital instability. Warren (2004) found British women working part-time reported more leisure time but greater financial strains than women pursuing full-time careers.…”
Section: Hypothesized Effects Of Employment On Divorce Risk In Contextmentioning
confidence: 99%
“…A 4-6 órás munkavégzés kedvezőtlen hatásai közül a leggyakrabban említik, hogy egyrészt sérül a nemek közötti egyenlőség a karrierépítési és továbbképzési lehetőségek korlátozottságából adódóan (például a vezetői pozíciók jellemzően teljes munkaidős állások, továbbá a részállású munkavállalókra kevésbé stabilan épít a munkaadó), másrészt fenntartja és legitimizálja a nőkre háruló kettős leterheltséget, továbbá az alacsonyabb fizetés szűkösebb lehetőségeket biztosít a megtakarításra, valamint a DOI: 10.14267/phd.2015028 18 rövidebb munkaidő a nyugdíjszerzésre való képességet szintén csökkenti (Hakim 2006;Tilly 1992;Warren 2004). A szakértők másik csoportja (Crompton 2002;Hochschild 2001; O'Reilly-Böthfeld 2002) a (női) munkavállalás előnyeit emeli ki a részmunkaidős állásokkal kapcsolatban, miszerint a felelősségteljes és önálló munkahelyi feladatok kedvezően hatnak a személyiségre, amely pozitív hatása az otthoni/munkahelyen kívüli környezetben is érvényesül.…”
Section: Atipikus Foglalkoztatásunclassified